(untitled) (Anclajes, 2024)
From a qualitative paradigm of a phenomenological nature and the symbolic and affective power of the epistolary text, we reflect on the experiences and feelings present in the letters that Rosario Castellanos wrote to her partner, Ricardo Guerra, to reflect about the captivities built through this correspondence. We start with the patriarchal structure and the category of captivity (Lagarde) in two dimensions: the private, regarding their love relationship, and the public, related to their academic relationship. These demands persist in the lives of women today, and they invite us to think that, although they have become more visible and their change is sought after, their structures and conditions continue to hamper a move away from these forms of domination.